The Impact of Benthic Processes on Rare Earth Element and Neodymium Isotope Distributions in the Oceans - Haley, Brian A.; Du, Jianghui; Abbott, April N.; McManus, James (Frontiers in Marine Science, 2017)
Neodymium (Nd) isotopes are considered a valuable tracer of modern and past ocean circulation. However, the promise of Nd isotope as a water mass tracer is hindered because there is not an entirely self-consistent model of the marine geochemical cycle of rare earth elements (REEs, of which Nd is one). That is, the prevailing mechanisms to describe the distributions of elemental and isotopic Nd are not completely reconciled. Here, we use published [Nd] and Nd isotope data to examine the prevailing model assumptions, and further compare these data to emergent alternative models that emphasize benthic processes in controlling the cycle of marine REEs and Nd isotopes. Our conclusion is that changing from a "top-down" driven model for REE cycling to one of a "bottom-up" benthic source model can provide consistent interpretations of these data for both elemental and isotopic Nd distributions. We discuss the implications such a benthic flux model carries for interpretation of Nd isotope data as a tracer for understanding modern and past changes in ocean circulation.